Low-level expression of SOD1 in peripheral blood samples of patients diagnosed with primary open-angle glaucoma. (December 2016) - Canizales, Licelly; Rodriguez, Laura; Rivera, Carlos; Martinez, Alexander; Mendez, Fabián; Castillo, Andres
Aim: Glaucoma is a multifactorial disease of retinal ganglion cells, with low prognosis. For that reason, the identification of biomarkers in peripheral blood samples for diagnostics and treatment of the disease is needed. To establish mRNA expression level of several oxidative stress biomarkers reported in aqueous humor of patients with primary open-angle glaucoma (POAG).Materials & methods: The mRNA expression levels of eight genes from 15 patients diagnosed with POAG and 11 control subjects were analyzed using an RT 2 Custom Profiler PCR Array.Results: mRNA expression level of superoxide dismutase 1 (SOD1) showed a significant downregulation in patients diagnosed with POAG in respect to control subjects. The low expression of SOD1 found in blood is consistent with the reported proteomic levels in aqueous humor.Conclusion: SOD1 may be a useful biomarker in the peripheral blood of patients diagnosed with POAG.